2015
DOI: 10.3747/co.22.2013
|View full text |Cite
|
Sign up to set email alerts
|

Using the Cancer Risk Management Model to Evaluate Colorectal Cancer Screening Options for Canada

Abstract: strategies, fobt parameter values associated with high-sensitivity formulations were associated with a substantial increase in test effectiveness. The fit was more cost-effective at the 50 ng/mL threshold than at the 100 ng/mL threshold. ConclusionsThe crmm-crc provides a sophisticated and flexible environment in which to evaluate crc control options. All screening scenarios considered in this study effectively reduced crc mortality, although sensitivity analyses demonstrated some uncertainty in the magnitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 55 publications
(52 reference statements)
1
24
0
Order By: Relevance
“…To facilitate policymakers' decision, a number of cost-effectiveness analyses assessing FIT have emerged [4346], with 2 studies assessing FIT cut-offs across a range of 50 to 100 ng/mL [45] and 50 to 200 ng/mL [46]. Both models found that a FIT cut-off of 50 ng/mL was the most cost-effective strategy.…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate policymakers' decision, a number of cost-effectiveness analyses assessing FIT have emerged [4346], with 2 studies assessing FIT cut-offs across a range of 50 to 100 ng/mL [45] and 50 to 200 ng/mL [46]. Both models found that a FIT cut-off of 50 ng/mL was the most cost-effective strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In the early 1990s, Statistics Canada developed the Population Health Model to "assist in the evaluation of cancer control interventions and policy decision-making" 1 , with a focus on lung 2,3 , breast [4][5][6] , and colorectal cancers 7 . More recently, the Canadian Partnership Against Cancer developed the Cancer Risk Management Model to "gain insight into the cost/benefit of cancer control strategies to help guide and strengthen decision-making" 8 , with a focus on lung 9 and colorectal cancers 10 . Other Canadian researchers have focused on prostate cancer 11,12 or the 21 most common cancers (brain, female breast, cervix, colorectal, corpus uteri, esophagus, gastric, head-and-neck, leukemia, liver, lung, lymphoma, melanoma, multiple myeloma, ovary, pancreas, prostate, renal, testis, thyroid, and urinary bladder) 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…The cervical cancer model in CRMM is more complex than the lung and colorectal cancer models [11,12] because the development of cervical cancer depends on HPV infection and individuals must come in contact with one another for the disease to spread. For cervical cancer two coupled models were built, one for the infectious spread of HPV within a population, including the effects of vaccination (CRMM-HPV) and the other for the pathway from infection to disease onset, progression, screening, treatment, and mortality (CRMM-Cervical).…”
Section: Introductionmentioning
confidence: 99%
“…The initial priorities were the development of a microsimulation model to evaluate the future burden of cancer in Canada, focusing on areas where it was felt progress could be made. The first two disease-specific models completed were on lung and colorectal cancer [11,12]. In view of the major investment in screening for cancer of the cervix in Canada it was decided that a model for cervical cancer could provide input into the development of policies for organized screening and dovetail into the policy of promoting vaccination of teenage girls against human papillomavirus (HPV) types 16, 18, 6 and 11, initiated Cancer of the uterine cervix is unique among cancers as it has a single necessary cause, infection with an oncogenic human papillomavirus (HPV) [13].…”
Section: Introductionmentioning
confidence: 99%